Technology in Western civilization (Oxford University Press, 1967)
Technology has been one of the major determinants in the development of Western civilization; yet only recently has there been recognition of the fact. As yet this recognition has not been sufficiently incorporated either into general histories of Western civilization, or into those books which deal specifically with the history of technology itself...